Home visits in rural areas: demands in primary care - Bruna Aparecida Rodrigues Duarte; Tayná Cristina Porto Leite; Thallys Rodrigues Félix; Marcela Santana; Carla Denari Giuliani (Rural and Remote Health, 2023)
Introduction: The rural population suffers from important limitations in accessing health care, often lacking a public policy approach to the health and sanitation conditions of their environment. In this sense, primary care emerges with the objective of offering comprehensive care to the population, applying some of its principles as territorialization, person-centered care, longitudinality, and resolution in health care. The goal is to offer the basic health needs of the population considering the determinants and conditions of health in each territory.Methods:The present study is an experience report that aimed to raise the main health demands of the rural population in the areas of nursing, dentistry, and psychology of a village in the state of Minas Gerais through home visits carried out as part of primary care.Results:Depression and psychological exhaustion were identified as the main psychological demands. Related to nursing, the difficulty of controlling chronic diseases was notable. Regarding dental care, the high prevalence of tooth loss was evident. In an attempt to minimize the limitations of access to health care, some strategies were created targeting the rural population. A radio program that aimed to disseminate basic health information in an accessible way was the main one.Discussion: Therefore, the importance of home visits is evident, especially in rural areas, favoring educational health and preventive practices in primary care and considering the adoption of more effective care strategies for rural populations.